MO176: Study of Urinary Monocyte Chemoattractant Protein-1(MCP-1) Level in Morbidly Obese Patients before and After Bariatric Surgeries and its Relation to Renal Function. (3rd May 2022) - Sabry, Alaa; Eldeep, Ahmed
Abstract: BACKGROUND AND AIMS: To assess the level of renal inflammatory marker monocyte chemoattractant protein -1(MCP-1), measure the urinary MCP to urinary creatinine concentration ratio in morbidly obese patients before and after bariatric surgeries. To study if there any possible relation between the MCP1 levels and renal function before and after surgery. METHOD: This prospective study of 40 morbidly obese patients undergoing bariatric surgery was recruited in the study in the interval between October 2018 and July 2019. Evaluate the level of MCP-1, urinary creatinine, urinary albumin, glomerular filtration rate, body weight, body mass index, CRP, serum albumin, blood pressure and lipid profile before and after 3 months of bariatric surgeries. RESULTS: The mean urinary level of MCP1 preoperative was 105.19 ± 15.25 pg/mL (range between 75.41 and 131.67) and this level was decreased postoperatively to 74.20 ± 22.77 (range between 30.5 and 114.4) with high statistically significant difference ( P  < .001). While urinary MCP1/creatinine ratio, bariatric surgery significantly reduced the mean of urinary MCP1/creatinine ratios from 2.08 ± 1.43 to 0.86 ± 0.51 ( P < 0.001). Significant improvement of blood pressure, CRP, lipid profile and body mass index after bariatric surgeries. CONCLUSION: We reported that urinary MCP-1 levels following bariatric surgery can be used as potential marker to the ongoing renal inflammatory process.